AB0156 Increased Soluble Semaphorin 4D in Rheumatoid Arthritis. (10th June 2014) - Yoshida, Y.; Ogata, A.; Tomita, T.; Kang, S.; Hirano, T.; Shima, Y.; Narazaki, M.; Tanaka, T.; Kumanogoh, A.
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune and inflammatory disorder of joints, which characterized with periarticular bone resorption. Recently cross-disciplinary field osteoimmunology was established because of reciprocal interactions between the immune and skeletal systems. To date, it is well known that inflammatory cytokines such as IL-6 and TNF stimulate bone resorption directly or through RANKL pathway. Recently semaphorins are thought to be new players in osteoimmunology. Sema4D that is produced by osteoclasts inhibits osteoblastgenesis and Sema3A that is produced by osteoblasts inhibits osteoclastgenesis. We previously reported Sema4D activate not only B cells, but also macrophage/monocytes, and induce proinflammatory cytokine production. These findings suggest that Sema4D plays an important role in the pathogenesis of RA and become a promising therapeutic target of RA. Objectives: To investigate the role of Sema4D in RA patients. Methods: The soluble Sema4D levels in sera and synovial fluid from patients with RA and osteoarthritis (OA) were measured by ELISA. Synovial fluid cells and peripheral blood cells from patients with RA were analyzed by flow cytometry. Sema4D expression of synovium were also observed by histological and immunohistochemical methods. Results: Serum levels of soluble Sema4D were increased in RA in comparison to healthy individuals (11.1±8.5 ng/ml and 5.7±2.7 ng/ml, respectively; p<0.0001). Serum levels of soluble Sema4D in OA and other diseases were slightly increased but it's not significant. In synovial fluid, soluble Sema4D were detected similarly in sera of RA (11.8±7.0 ng/ml). In contrast, Sema4D was not detected in synovial fluid of OA. The levels of serum soluble Sema4D was correlated with disease activities of RA such as DAS28 (r=0.383, p<0.01), CRP (r=0.346, p<0.01), rheumatoid factor (r=0.328, p<0.01), and urinary deoxypyridinoline (r=0.318, p<0.05). The change of serum soluble Sema4D was correlated with the change of DAS28 in RA patients treated with bologics. The infiltrations of Sema4D expressing cells were observed in RA synovium. Compared to healthy individuals, the cell surface expression of sema4D was decreased in CD3+ cells and CD14+ cells in peripheral blood and synovial fluids of RA patients. The treatment with ADAMTS14, which is upregulated in RA patients reduce the expression of cell surface Same4D. In addition soluble Sema4D stimulates IL-6 and TNF-alpha production from PBMC. Conclusions: Soluble Sema4D was shown to be elevated in RA and is derived from T cells and monocytes in peripheral blood and synovial fluid by shedding from cell surface. Increased soluble Sema4D may play an important role in immune activation and bone resorpotion in RA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3513